A new genus of Neotropical Chrysopini (Neuroptera: Chrysopidae) - Sosa, Francisco; De Freitas, Sergio [UNESP] (Magnolia Press, 2012)
Titanochrysa Sosa & Freitas is a new genus of Neotropical Chrysopini (Chrysopidae: Chrysopinae) recorded from Costa Rica, Venezuela and Brazil. Titanochrysa gen. nov. shares several external and genitalic characters with Ceraeochrysa Adams, 1982; Chrysopodes Navás, 1913; Cryptochrysa Freitas & Penny, 2000; Parachrysopiella Brooks & Barnard, 1990 and Ungla Navás 1914. It may be distinguished from those genera by its very long sternite 8+9, sternites 2-8 usually with microtholi, male genitalia with the dorsal surface of the arcessus striated, gonosaccus well-developed, bearing elongate gonosetae and microsetae, and a spoon-like gonapsis. Herein, Titanochrysa circumfusa (Burmeister, 1939) [= Chrysopodes circumfusa (Burmeister)] comb. nov. and Titanochrysa pseudovaricosa (Penny) [= Ceraeochrysa pseudovaricosa Penny, 1998] comb. nov. were identified; Titanochrysa ferreirai Sosa & Freitas sp. nov. and Titanochrysa trespuntensis Sosa & Freitas sp. nov. were described. The external morphology, and male and female genitalia of all these species are described. Titanochrysa circumfusa (Burmeister, 1939) comb. nov. is recorded for the first time from Venezuela. Copyright © 2012 · Magnolia Press.
Keywords: Chrysopinae; Chrysopini; Green lacewing; Predator